KENDALA KERJASAMA MERIDA INITIATIVE DALAM PENANGANAN PENYELUNDUPAN SMALL ARMS AND LIGHT WEAPONS (PERIODE 2008-2012) - Virgiyanti, Zaqia Indah; Utomo, Tri Cahyo (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
Transnational crime is an important issue because the threat impacts take place across the borders of two or more countries. Armed violence by the Mexican Drugs Trafficking Organization is increasingly threatening the security of Mexico, due to the access of weapons smuggled from United States. The Merida Initiative was signed in 2008 with the aim of adressing the threat of transnational organized crime. But in 2007-2012, the number of smuggling of weapons continues to increase. This research then aims to analyze the constraints on Merida Initiative implementation in combating the smuggling of small arms and light weapons. This research uses the neoliberalism paradigm in understanding the inhibiting factors of the success of a cooperation, thus explaining the cause of the increased number of smuggling weapons after Merida Initiative was signed. The results showed that the inhibiting factor in combating the smuggling of small arms and light weapons is the absence of mutuality of interest. The absence of mutuality of interest is explained by the responses that are given not in accordance of what was expected from other country. The absence of mutuality of interest results in a tendency for a state to prioritize the national interest above the common interest.